Realisasi Tindak Komisif Pada Debat Cagub Dan Cawagub DKI Jakarta 2017 Dan Implementasinya Sebagai Bahan Ajar Sekolah Menengah Kejuruan - Wahdania, Eria Winda, Prof Dr Harun Joko Prayitno (2017)
This research describes form of commissive speech acts in discourse debate Cagub and Cawagub DKI Jakarta 2017, the strategy of commissive speech acts in discourse debate Cagub and Cawagub DKI Jakarta 2017 and describe the implications of commissive speech acts in discourse debate Cagub and Cawagub DKI Jakarta as teaching materials Senior High School. Techniques of collecting data using techniques refer and record. Data analysis using the fifth sub-type fifth method is pragmatic method with speech determinator. Data validity using triangulation. The results of this study show that the most intensive form of combat action among other forms of comic action. Speaking strategies used by candidate pairs more often are direct-talking strategies. This research can also be implemented on high school teaching materials in commenting subjects in discussions or seminars, its function is as an example of good or correct responses or comments